Is God a Phenomenon? A dialogue between Kierkegaard and Jean-Luc Marion - Santana, Wellington José (Philósophos - Revista de Filosofia, 2020)
The present article analyses critically the paradox of phenomenon claimed by Danish Philosopher Kierkegaard and Marion’s new concept named saturated phenomenon. While the concept of God, by definition, must surpass the realm of empiricism, perhaps the something may shed light over what God must be: Excess. However, Marion developed a new concept of phenomenon that not only occupies the immanence world, but also goes beyond. It is called saturated phenomenon. In order to address the question one might understand the limit of the givenness and then what does it mean saturated givenness. We probably all have had the sense of being overwhelmed by something and this can lead toward a sense of torpor or numbness. In the other hand, Kierkegaard affirms that God is so different than a human being, so totally other that we may think we’re right in demanding God make himself understood and be reasonable towards us. Kierkegaard upholds that we’re always dealing with God in the wrong way. I will argue that Marion, however, following phenomenological footsteps indicates a new path toward how to address God properly. Key words: Paradox; Saturated phenomenon; freedom; Excess.